2020
DOI: 10.32479/irmm.10806
|View full text |Cite
|
Sign up to set email alerts
|

Social Media and Employee Productivity at Workplace

Abstract: This study makes theoretical contributions related to social media usage in the workplace. Participants who showed high work performance used social media to help communicate with their colleagues. People showed high work performance were also the ones escaping from an unsatisfying job for a while and escaping from a demanding job for a while by using social media in the workplace. High frequency of using social media in the workplace resulted in increased work performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Previously researchers had mixed opinion about the relationship between use of social media and employee productivity. Celebi and Terkan (2020) stated that use of social media at workplace enhances employee-employee communication, work efficiency and productivity. Some other researcher (Nduhura & Prieler, 2017;Robertson & Kee, 2017;Tajudeen et al, 2018;Tulu, 2017;van Zoonen et al, 2016) also found positive relationship between social media usage and workplace performance.…”
Section: Use Of Social Media and Employee Productivitymentioning
confidence: 99%
“…Previously researchers had mixed opinion about the relationship between use of social media and employee productivity. Celebi and Terkan (2020) stated that use of social media at workplace enhances employee-employee communication, work efficiency and productivity. Some other researcher (Nduhura & Prieler, 2017;Robertson & Kee, 2017;Tajudeen et al, 2018;Tulu, 2017;van Zoonen et al, 2016) also found positive relationship between social media usage and workplace performance.…”
Section: Use Of Social Media and Employee Productivitymentioning
confidence: 99%
“…Some study found that using cyberspace at work significantly reduces employees' productivity due to time spent online chatting with friends, exchanging photos, gaming and interacting with coworkers (Wushe and Shenje, 2019). The study by (Celebi and Terkan, 2020) shows that social media usage does not increase work performance, nor does it improves employee's productivity. Excessive internet usage not only impacts on the work productivity but generally social occupational functioning of an individual especially disturbance in sleep, meals, personal hygiene and family relationships are also negatively impacted (Shrivastava et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%